Potencial alelopático de extratos de folhas de Geonoma schottiana (Arecaceae) - Gomes, Alessandro Bermudes (2016)
Brazil is the country with the largest plant genetic diversity in the world and bioprospecting research of native species can contribute significantly to the economic and environmental development of the nation's agricultural sector, among many other areasof human activity. Thus, the present study aimed to verify the allelopathic potential of aricanga palm (Arecaceae), native of the Atlantic Forest and endemic of Brazil. Leaf extracts of Geonomaschottianawere used in the germination of a cultivated plantand other weeds (Lactucasativa L. and Panicum maximum, respectively). The leaves were macerated using as extractants the methanol, ethyl acetate and hexane for seven days. After this procedure, the solvent was evaporated and were prepared three concentrations (0 mg/L, 200mg/L, 400mg/L and 800mg/L). From there onwards were evaluated percentages of germination, germination speed index, length of radicles and leaves and mitotic index, as well as phytochemical screening for the detection of chemical groups present in the extracts. All parameters wereaffected by both extracts, on lettuce as well as on the guinea grass. The methanol and ethyl acetate extracts showed significant reduction of the mitotic index from 400 mg / L, while in the hexane extract that occurred from 200 mg / L. In phytochemical found coumarins, alkaloids, steroids and flavonoids in methanol extracts and ethyl acetate , and only steroids and flavonoids in hexane extract.These results indicate a significant potential allelopathic leaf Geonoma schottiana